Onsite Sewage Treatment and Disposal Systems: Nitrogen - Gurpal S. Toor; Mary Lusk; Tom Obreza (EDIS)
In the United States, about 4,800 water bodies are impaired due to excess nitrogen (N), and septic systems are recognized as one source of N pollution. This 6-page fact sheet describes the behavior and transport of N from a conventional septic system and the summarizes the sources of N in sewage, the forms and behavior of N in septic tanks and drain fields, and the fate and transport of N in groundwater. Written by Gurpal Toor, Mary Lusk, and Tom Obreza, and published by the UF Department of Soil and Water Science, June 2011.